Molecular genetics of bacteria - Dale, Jeremey W. (John Wiley & Sons, 1998)
Molecular Genetics of Bacteria Third Edition Jeremy W. Dale School of Biological Sciences, University of Surrey, UK This third edition of Jeremy Dale's successful book provides a thoroughly updated and revised introduction to the molecular biology and genetics of bacteria. Molecular Genetics of Bacteria presents both the basic concepts and the most exciting recent developments in a form which is suitable for the needs of students studying microbiology, biotechnology, molecular biology, biochemistry, genetics and related biomedical sciences. The structure of the third edition has undergone a major reorganization and incorporates: New material on the concept of adaptive mutation, bacterial differentiation, intercellular signalling, conjugative transposons and integrons. Enhanced coverage of supercoiling, reporter genes, sporulation, PCR and genome sequencing projects. Reviews of the Second Edition: "I recommend this book strongly for the purpose for which it was designed, namely as an introductory text with broad coverage of the subject." Simon Baumberg, University of Leeds, Society for General Microbiology Quarterly ". a text that is readable and attractive to people who may be daunted by more-detailed works.